New considerations on a particular iconographic scheme of the Orientalising period in Etruria (Aristonothos. Rivista di Studi sul Mediterraneo Antico, 2022)
In questo lavoro verrà preso in considerazione un particolare schema iconografico riconoscibile su un piccolo numero di materiali etruschi databili al VII secolo a.C.A rendere particolarmente rilevante questo schema è la diffusione geografica che esso presenta con due differenti poli, uno padano e uno meridionale, strettamente vulcente. Ciò appare rilevante soprattutto considerando quanto è stato osservato in passato a proposito dei contatti tra Vulci e l’Etruria padana dal punto di vista epigrafico. A particular iconographic scheme can be identified on a small number of Etruscan objects datable to the 7th century BCE. What makes this scheme particularly relevant is its diffusion between two geographical poles: the Po Valley and South Etruria, particularly at Vulci. These objects are important indicators of a pattern of contacts similar to that previously observed between Vulci, North Etruria, and the Po Valley from an epigraphic point of view.
Keywords: Etruria; orientalising period; iconography; contacts